Kinetic pupillary size using Pentacam in myopia - Li, Kaixiu; Li, Xiaoqi; Wang, Qun; Wang, Liqiang; Huang, Yifei (Frontiers in Neuroscience, 2022)
Purpose To compare if the kinetic pupillary changes differs between high myopia (HM) and low/moderate myopia by Pentacam. Setting Chinese People’s Liberation Army (PLA) General Hospital, Beijing, China. Design Comparative study. Methods In this cross-sectional retrospective study, 44 eyes of 44 patients were recruited in the Refractive Surgery Center of Chinese PLA General Hospital. Eyes were divided into two groups according to the refractive error: low/moderate myopia (22 eyes; −2.99 ± 1.09 D) and HM (22 eyes, −12.93 ± 3.44 D). At the beginning of the experiment, we made trials of scanning one false pupil by Pentacam. All patients underwent the Pentacam examination three times. Pupillary diameters (PD) during the scan process and other parameters were measured using the Pentacam. Coefficient variations of PD (CV) during the different scanning periods were analyzed comparatively between the two groups. Results Pentacam once time output 25 Scheimpflug images, with 13 ones during the period from 1st to 1.5th s and 12 ones during the period from 2.5th to 3rd s after the scanning onset. For the spatial order on all the 25 meridians, 13 Scheimpflug images came out when the Pentacam rotated from 60° to 153°meridians and the remaining 12 Scheimpflug images from 161° to 245° meridians. Among pupillary parameters, no statistical significance existed in PD25, PD13, and PD12 (pupil diameter’s mean from all, former 13 and remaining 12 of 25 Scheimpflug images, respectively) (P > 0.05) between the two groups. However, there were statistically significant differences in CV25 and CV13 (coefficient variation of the pupil diameters from all and former 13 of 25 images, respectively) (P < 0.001), with no statistical significance in CV12 (coefficient variation of the pupil diameters from remaining 12 of 25 images) between both groups. Conclusion Twenty-five Scheimpflug images on Pentacam had the temporal and the spatial orders. CV in eyes with HM was lower than that in eyes with low/moderate myopia in a certain period of the Pentacam scan. Kinetic pupillary size in HM changed more slowly than that in low/moderate myopia during some scanning period analogous to the phasic response of the pupil reflex.